Joe golem: occult detective (2015), volume 2 ebook Occult detective volume 2--the outer dark. - Golden, Christopher (Joe Golem: Occult Detective (2015), 2018)
Occult detective Joe Golem invesitgates two supernatural mysteries, while demons from his past seep into the present. When men are being driven mad by otherworldy voices in their heads, Joe's search for an explanation leads to another dimension, and a dangerous man who wants to harness its power. Then, Church leads Joe to a crumbling home where a young woman is being possessed by the ghosts of her family. Collects Joe Golem: The Outer Dark #1-3 and Joe Golem - Flesh and Blood #1-2.